Improvement of kidney redox states contributes to the beneficial effects of dietary pomegranate peel against barium chloride-induced nephrotoxicity in adult rats. (26th May 2016) - Elwej, Awatef; Ghorbel, Imen; Marrekchi, Rim; Boudawara, Ons; Jamoussi, Kamel; Boudawara, Tahia; Zeghal, Najiba; Sefi, Mediha
Abstract: Context : Pomegranate ( Punica granatum L., Punicaceae) is known to possess enormous antioxidant activity. Objective : This study investigates the protective effects of pomegranate peel against barium-mediated renal damage. Materials and methods : Rats were exposed during 21 days either to barium (67 ppm), barium + pomegranate peel (5% of diet) or to only pomegranate peel (5% of diet). Results : Exposure rats to barium provoked a significant increase in kidney malondialdehyde (MDA), advanced oxidation protein products (AOPP) and hydrogen peroxide (H2 O2 ) levels. Creatinine, urea and uric acid levels in plasma and urine were also modified. Superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) activities, non protein thiol (NPSH) and reduced glutathione (GSH) levels were decreased. Metallothionein (MT) production was increased and their genes expressions were up-regulated. All these changes were improved by dietary pomegranate peel. Moreover, the distorted histoarchitecture in kidney of barium group was alleviated by pomegranate peel. Conclusion : Our data showed, for the first time, the protective effects of pomegranate peel against barium-induced renal oxidative damage.